Optimal allocation of a limited resource - Voronin, A.; Savchenko, A. (Проблеми керування та інформатики, 2023)
In various subject areas, the problem arises of such a distribution of a limited resource between the elements (objects) of the system, in which the system as a whole functions in the best possible way. Often this task is solved subjectively, based on the experience and professional qualifications of the decision maker (DM). In simple cases, this approach may be justified. However, with a large number of objects and in critical cases, the price of an error in a management decision increases sharply. It becomes necessary to develop formalized decision support methods for the competent distribution of resources between objects, taking into account all given circumstances. Many of such circumstances are usually limited resources. У різних предметних областях виникає проблема такого розподілу обмеженого ресурсу між елементами (обʼєктами) системи, за яким система в цілому функціонує якнайкраще. Часто ця проблема вирішується субʼєктивно, на основі досвіду та професійної кваліфікації особи, яка приймає рішення (ОПР). У найпростіших випадках такий підхід може бути виправданим. Однак за великої кількості обʼєктів і у відповідальних випадках різко зростає ціна помилки управлінського рішення. Стає необхідною розробка формалізованих методів підтримки прийняття рішень для грамотного розподілу ресурсів між обʼєктами з урахуванням усіх обставин. Багато з таких обставин — зазвичай обмежені ресурси.